PENGARUH CUSTOMER REVIEW DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MIE NYINYIR PADA APLIKASI SHOPEE FOOD - Ambarwati, Arum; Nissa Khoiri, Aulia; Rahma Dewi, Nafisa; Lailatul Habiba, Nazilah; Prastiti, Wintan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Mie Nyinyir is one of the popular online and offline culinary in Yogyakarta. Although there are some branches of store, they always full of orders. This study aims to analyse the influence of customer reviews and sales promotions on consumers purchasing decisions. This study used quantitative methods, by distributing questionnaires. The samples were 41 respondents of Mie Nyinyir consumers. The analysis method used instrument tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and determination coefficient tests. The results showed that customer reviews and sales promotions have a positive and significant impact on purchasing decisions.